The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/clc.23447
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ventricular pacing burden after permanent pacemaker implantation following transcatheter aortic valve replacement

Abstract: Background: In the era of an expanding use of transcatheter aortic valve replacement (TAVR), conduction disturbances and the requirement for permanent pacemaker (PPM) implantation remains a clinical concern. Hypothesis: Using a single-center experience, we sought to identify predictors of ventricular pacing burden after TAVR in patients who required PPM implantation. Methods: We conducted a retrospective study of 359 consecutive patients with symptomatic severe aortic valve stenosis who underwent TAVR at our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 54 Other factors were found to predict a high percentage of long-term pacing in patients who experienced post-TAVI PPI such as high left ventricular outflow tract diameter ratio, high aortic annulus diameter ratio, new onset of left bundle branch block, time to PPI >2 days, and therapy with beta-blockers. 55 Consequently, the choice of intervention modality in patients with AS should take into account the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“… 54 Other factors were found to predict a high percentage of long-term pacing in patients who experienced post-TAVI PPI such as high left ventricular outflow tract diameter ratio, high aortic annulus diameter ratio, new onset of left bundle branch block, time to PPI >2 days, and therapy with beta-blockers. 55 Consequently, the choice of intervention modality in patients with AS should take into account the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, recovery of AV node conduction was found in 50–73% of patients [ 13 , 20 ], thus superior to the rate observed in our population. Most studies defined PM non-dependency as VP < 5%, as we straightforwardly did [ 21 ]. It is worth mentioning that the percentage of VP may generally be influenced by different factors, including increased overnight pacing and “out of the box”, standardized algorithms which threaten tailored ones.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the above factors have been proven to be predictors of new conduction block after TAVR, with the prosthesis implantation depth the most relevant risk factor. Other risk factors including the type of valve implanted, overexpansion of native annulus, the occurrence of right bundle branch block (RBBB) at baseline, preexisting LVOT calcification, preexisting first-degree AVB and prolonged baseline QRS duration, previous coronary bypass and female gender [15][16][17]. The presence of RBBB at baseline was one of the important predictors.…”
Section: Pathogenesis Predictive Factors Of New Onset Lbbbmentioning
confidence: 99%